2016
DOI: 10.18549/pharmpract.2016.01.713
|View full text |Cite
|
Sign up to set email alerts
|

Inter-professional education unveiling significant association between asthma knowledge and inhaler technique

Abstract: Objectives:To explore whether an association exists between health care professionals’ (HCPs) asthma knowledge and inhaler technique demonstration skills.Methods:HCPs’ asthma knowledge and inhaler technique demonstration skills were assessed at baseline at an inter-professional educational workshop focusing on asthma medication use. Asthma knowledge was assessed via a published questionnaire. Correct inhaler technique for the three inhalers, the Accuhaler, Turbuhaler and pressurized Metered Dose Inhaler (pMDI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Many prior studies have reviewed inhaler technique for nurses working in a wide variety of departments including medical, respiratory, intensive care, emergency, and community settings, and other HCPs such as pharmacists, doctors and respiratory therapists. 16 , 20 , 21 However, to our knowledge, this study is the first that has examined the relationships between the total correct device steps, years of nursing, self-reported confidence and total hospital-prescribed inhaler device in nurses from a specialised respiratory ward. The lack of correlation between correct technique and years of experience or confidence suggests a need to improve the inhaler competence of all nursing staff with a particular focus on training for newer and/or less often prescribed inhaler devices to improve patient care, irrespective of nurses’ perceived confidence in inhaler technique or their level of nursing experience.…”
Section: Discussionmentioning
confidence: 98%
“…Many prior studies have reviewed inhaler technique for nurses working in a wide variety of departments including medical, respiratory, intensive care, emergency, and community settings, and other HCPs such as pharmacists, doctors and respiratory therapists. 16 , 20 , 21 However, to our knowledge, this study is the first that has examined the relationships between the total correct device steps, years of nursing, self-reported confidence and total hospital-prescribed inhaler device in nurses from a specialised respiratory ward. The lack of correlation between correct technique and years of experience or confidence suggests a need to improve the inhaler competence of all nursing staff with a particular focus on training for newer and/or less often prescribed inhaler devices to improve patient care, irrespective of nurses’ perceived confidence in inhaler technique or their level of nursing experience.…”
Section: Discussionmentioning
confidence: 98%
“…Use of inhaler technique labels also provides an effective method for maintaining the inhaler skills of health professionals themselves. Many health professionals are not able to demonstrate correct inhaler technique, 31 and, like patients, their skills fall off after training. 32 34 However, we have previously shown that community pharmacists engaged in regularly checking their clients’ inhaler technique with checklists and inhaler labels maintained their own technique 2 years after a brief workshop.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Results from a recent study found that the knowledge of HCPs, including pharmacists, about asthma was significantly associated with inhaler demonstration skills. 66 Consequently, providing pharmacists with effective education tools and specific training on asthma and inhaler technique will ensure that they can play a pivotal role in educating patients on correct inhaler techniques. 67 Such training is essential because only a small proportion of patients receive information on inhaler use, with an even smaller proportion of patients having their inhaler technique checked over time.…”
Section: Introductionmentioning
confidence: 99%